2022
DOI: 10.1002/pbc.30034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response to lifestyle counseling for dyslipidemia and elevated blood pressure in childhood cancer survivors

Abstract: Background Childhood cancer survivors (CCS) have increased risk of premature cardiovascular disease. Whether they respond similarly to lifestyle changes for elevated blood pressure (BP), body mass index (BMI), and dyslipidemia to those without history of childhood cancer is unknown. Procedure This retrospective cohort study included CCS and 3:1 age‐ and sex‐matched controls treated at Boston Children's Hospital Preventive Cardiology (2010–2019) using lifestyle management based on National Heart, Lung, and Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Generalizability of any intervention to a primary care setting must consider regional, cultural, and socioeconomic factors and draw on expertise from dissemination and implementation science. Moreover, evidence on the importance of tailoring lifestyle interventions to survivorship 77 brings into question the translation of pharmacotherapy guidelines from the general population to survivors, necessitating survivor-specific trials with novel study designs to evaluate the safety and effectiveness of available treatments in this unique patient population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generalizability of any intervention to a primary care setting must consider regional, cultural, and socioeconomic factors and draw on expertise from dissemination and implementation science. Moreover, evidence on the importance of tailoring lifestyle interventions to survivorship 77 brings into question the translation of pharmacotherapy guidelines from the general population to survivors, necessitating survivor-specific trials with novel study designs to evaluate the safety and effectiveness of available treatments in this unique patient population.…”
Section: Discussionmentioning
confidence: 99%
“…For managing dyslipidemia in survivors, a retrospective study observed improved triglyceride levels in survivors in response to adopting lifestyle modifications guidelines from the general pediatric population. 77 However, among the trials listed in Supplemental Table 1 , those measuring lipid levels as a secondary outcome did not report significant changes regardless of the effect on weight. 60 , 62 , 63 , 65 , 78 , 79 …”
Section: Dyslipidemiamentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, almost all CCS (97%) consider lifestyle counseling useful as part of care. It is important to inform CCS about their increased risk of developing metabolic diseases such as dyslipidemia, hypertension, diabetes mellitus or obesity (8,11). A healthy lifestyle including regular physical activity and nutrient and vitamin rich diet can reduce this risk (36).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, multiple studies evaluated the effect of counseling on the CCS lifestyle and could demonstrate a reduction in co-morbidities as well as a better quality of life due to a healthy lifestyle (9,10). Furthermore, CCS improved in blood pressure due to lifestyle counseling in previous studies (11). Therefore, a healthier lifestyle could result in less co-morbidities including the metabolic syndrome among CCS (9).…”
Section: Introductionmentioning
confidence: 99%